Characterization of Population Genetic Structure of red swamp crayfish, Procambarus clarkii, in China - Yi, Shaokui; Li, Yanhe; Shi, Linlin; Zhang, Long; Li, Qingbin; Chen, Jing (Scientific reports, 2018)
The red swamp crayfish ( Procambarus clarkii ) is one of the most economically important farmed aquatic species in China. However, it is also a famous invasive species in the world. This invasive species was dispersed most via human activities including intentional or unintentional carry in China. Thus, P. clarkii naturally distributed in China provides us a desirable mode to investigate the genetic structure of an invasive species dispersed mainly by human-mediated factors. To reveal the impact of human-mediated dispersal on genetic structure of P. clarkii in China, a total of 22,043 genome-wide SNPs were obtained from approximately 7.4 billion raw reads using 2b-RAD technique in this study. An evident pattern of population genetic structure and the asymmetrical migrational rates between different regions were observed with 22 populations based on these SNPs. This study provide a better understanding of the population genetic structure and demographic history of P . clarkii populations in China, inferring that anthropogenic factors (aquaculture or by accident) and ecological factors (e.g., complicated topography and climatic environment), as well as its special biological traits could account for the current population structure pattern and dispersal history of P . clarkii .